MANAGEMENT OF DENTO-ALVEOLAR SURGICAL EMERGENCIES IN PEDIATRIC PATIENTS - Mircea Rivis; Alexandra Roi; Cristina Fuior; Cosmin Sinescu; Ciprian Roi (Romanian Journal of Oral Rehabilitation)
Aim of the study: The study aims to establish the particularities of the pediatric patients with dento-alveolar surgical emergencies, what types of emergencies are common and what treatment is applied. A closer investigation of “what is happening and why” is needed to explore the factors that contribute to the referral of families and their children to a public hospital over private practices, and why is a high demand for emergency dental care for children in recent years. Material and methods: The observational study is based on the data collected from the clinical records taken from 219 pediatric patients that presented in Emergency Department of Oral and Maxillofacial Surgery Clinic Timisoara. Results: The most frequent types of diagnosis in pediatric patients encountered in the Emergency Department are cases of odontogenic infections and trauma. Children between the ages of 13 and 18 are most exposed of the teeth decay complications. Cases of trauma were as common as infections of odontogenic origin. The dento-alveolar trauma occurred almost twice as often in boys than in girls. Conclusions: Accurate diagnosis, timely treatment and monitoring are essential for the management of dento-alveolar surgical emergencies in pediatric patients. The management of dento-alveolar emergencies in pediatric patients is a complex procedure that requires a complete and accurate diagnosis, as well as treatment planning, based on a multidisciplinary approach.